A comparative study of open and closed hemorrhoidectomy - Mohapatra, Raghunath; Murmu, Dasarathi; Mohanty, Alok (International Surgery Journal, 2018)
Background: Hemorrhoidectomy is the treatment of choice for patients with third-degree or fourth-degree haemorrhoids. This prospective randomized clinical study compared the outcome of surgical haemorrhoidectomy by open and closed techniques in terms of postoperative pain, wound healing, and morbidity. Methods: All consecutive patients with Grade III internal haemorrhoids or Grade IV haemorrhoids were randomly allocated to one of two groups. The entire wound was left open in the open group and completely closed using 2-0 chromic sutures in the closed group. Postoperative pain was assessed by a linear analog scale. Additional consumption of analgesics on the day of surgery and at defecation during the first week was recorded. Patients were followed up 1, 2, and 3 weeks after the procedure. Results: There were 30 patients in each group. No statistically significant differences were found between the two methods regarding complications, pain, or postoperative stay. There were four reoperations for bleeding, all after Milligan-Morgan operations. At follow-up after three weeks 78 percent of the Ferguson patients had completely healed wounds, and none had signs of infection. Of the Milligan-Morgan patients, only 26 percent had completely healed wounds, and symptoms of delayed wound healing were significantly more frequent. Conclusions: Both methods are fairly efficient treatment for third and fourth degree hemorrhoids, without serious drawbacks. The closed method has no advantage in postoperative pain reduction but is more advantageous with respect to faster wound healing.